2017
DOI: 10.1159/000477107
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA CRNDE Promotes Proliferation of Gastric Cancer Cells by Targeting miR-145

Abstract: Background/Aims: The colorectal neoplasia differentially expressed (CRNDE) gene is a long noncoding RNA (lncRNAs) that is upregulated in colorectal cancer and glioma. Here, we investigated the regulatory function of CRNDE in gastric cancer (GC). Methods: CRNDE and miR-145 expression were assayed by qRT-PCR, and E2F3 protein expression was measured by western blotting. A luciferase reporter assay was used to detect the direct regulation of miR-145 by CRNDE. Cell viability and colony formation of human GC cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 33 publications
1
59
0
Order By: Relevance
“…10,11 miR-154 is able to repress GC cell development by inhibiting MTDH. 38 LncRNA PVT1 can act as a competing endogenous RNA by sponging miR-186 in GC. 37 Many studies have indicated the correlation between lncRNAs and F I G U R E 4 miR-506 was a direct target of NEAT1.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 miR-154 is able to repress GC cell development by inhibiting MTDH. 38 LncRNA PVT1 can act as a competing endogenous RNA by sponging miR-186 in GC. 37 Many studies have indicated the correlation between lncRNAs and F I G U R E 4 miR-506 was a direct target of NEAT1.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand and identify efficient new biomarkers of COAD, we are studying the mechanisms of COAD. Recent studies have shown that lncRNAs play vital roles in the development of cancer [2,3,[18][19][20][21], but there have been very few studies that focused on the profiles of lncRNAs in CRC. lncRNAs mRNA targets HOTAIR REV3L, INO80D, PHIP, AGO3, TAOK1, ATM, GPATCH2L, RC3H1, SHPRH, RICTOR, MAP3K2, ATAD2B, RIC1, PIKFYVE, WDPCP, USP34, PHC3, MIR133A1HG, BRWD1, ZBTB37 LINC00355 ATM, REV3L, GPATCH2L, RICTOR, SHPRH, PHIP, AGO3, WDPCP, INO80D, RIC1, RC3H1, TAOK1, USP34, ATAD2B, MFSD4B, FAM217A, PIKFYVE, ZBTB37, NBEAL1, GDAP2 TSSC1-IT1 SHPRH, INO80D, LRRTM2, TNRC6B, GPATCH2L, PHC3, GPR52, RC3H1, AGO3, ZBTB20, REV3L, NBEAL1, RNF169, TAS2R19, MFSD4B, IFNK, CLDN20, RIC1, FBXL13, MATR3 KCNQ1OT1 SHPRH, INO80D, AGO3, LRRTM2, RC3H1, MIR133A1HG, GPATCH2L, REV3L, MATR3, ZBTB20, PHC3, GPR52, GDAP2, POU5F2, MFSD4B, NBEAL1, TAS2R19, ATM, C1orf195, AIRN LncRNAs have sophisticated functions through diverse pathways, and the ceRNA hypothesis makes the relationship between lncRNAs, miRNAs, and mRNAs more complicated.…”
Section: Discussionmentioning
confidence: 99%
“…11 Recent years, CRNDE had been suggested to be overexpression in most types of human malignancy including colorectal cancer, 6,12-16 gastric cancer, 17 cervical cancer, 27 lung cancer, 28 and acute myeloid leukemia. 11 Recent years, CRNDE had been suggested to be overexpression in most types of human malignancy including colorectal cancer, 6,12-16 gastric cancer, 17 cervical cancer, 27 lung cancer, 28 and acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%